Controlling of Optical Band Gap of Allyl Diglycol Carbonate Polymer with Ultraviolet Laser Radiation - Farooq, W. A.; Baig, M. R.; Fatehmulla, A.; Al-Salhi, M. S.; Al-Ghamdi, S. S.; Yakuphanoğlu, Fahrettin (Polish Acad Sciences Inst Physics, 2013)
The effects of ultraviolet laser radiation on the structure and optical properties of ally! diglycol carbonate have been investigated. The allyl diglycol carbonate samples were irradiated with 266 nm with different power densities from Nd:YAG laser. The bulk etch rate enhancement and enlargement of track diameter clearly indicate that allyl diglycol carbonate is significantly affected by UV laser. The laser-irradiated allyl diglycol carbonate samples showed a decrease in the optical band gap with increasing laser power density. The obtained results indicate that the optical band gap of the alpha irradiated polymer is varied from 4.10 eV to 2.65 eV by UV laser irradiation. DOI: 10.12693/APhysPolA.123.106
Keywords: Track Detector; Gamma-Rays; Cr-39; Irradiation